2008
DOI: 10.1186/1741-7007-6-12
|View full text |Cite
|
Sign up to set email alerts
|

Double-stranded RNA-activated protein kinase PKR of fishes and amphibians: Varying the number of double-stranded RNA binding domains and lineage-specific duplications

Abstract: Background: Double-stranded (ds) RNA, generated during viral infection, binds and activates the mammalian anti-viral protein kinase PKR, which phosphorylates the translation initiation factor eIF2α leading to the general inhibition of protein synthesis. Although PKR-like activity has been described in fish cells, the responsible enzymes eluded molecular characterization until the recent discovery of goldfish and zebrafish PKZ, which contain Z-DNA-binding domains instead of dsRNAbinding domains (dsRBDs). Fish a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
80
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(82 citation statements)
references
References 70 publications
2
80
0
Order By: Relevance
“…3B). PKR homologs in zebrafish and X. laevis have been reported previously, and have been shown capable of phosphorylating yeast eIF2a on Ser 51 (Rothenburg et al 2008). Our data here demonstrate that CBTF 98 and CTBF 122 are phosphorylated on T188 and T315, perhaps by a X. laevis PKRhomolog, in response to virus infection, plausibly indicating a conserved mechanism of cellular antiviral host response.…”
Section: Identification Of Thr 188 (T188) and Thr 315 (T315) In Nfar1supporting
confidence: 76%
See 1 more Smart Citation
“…3B). PKR homologs in zebrafish and X. laevis have been reported previously, and have been shown capable of phosphorylating yeast eIF2a on Ser 51 (Rothenburg et al 2008). Our data here demonstrate that CBTF 98 and CTBF 122 are phosphorylated on T188 and T315, perhaps by a X. laevis PKRhomolog, in response to virus infection, plausibly indicating a conserved mechanism of cellular antiviral host response.…”
Section: Identification Of Thr 188 (T188) and Thr 315 (T315) In Nfar1supporting
confidence: 76%
“…Of interest is that T188 and T315 are evolutionarily conserved in CBTF 98 and CBTF 122 and undergo phosphorylation in response to virus infection. PKR homologs have been reported in amphibians (Rothenburg et al 2008). Thus, phosphorylation of CBTF 98 and CBTF 122 on T315 and T188 may have been evolutionarily conserved.…”
Section: Discussionmentioning
confidence: 95%
“…miRNA pathway is the dominant small RNA pathway while the existence and functionality of endogenous RNAi are unclear. Some variations (DNA-binding PKR homologs (Rothenburg et al, 2008)) were found in the interferon system, which is the main fish antiviral system. The present document has been produced and adopted by the bodies identified above as authors.…”
Section: Discussionmentioning
confidence: 99%
“…3). The kinase domains of fish PKR genes are more closely related to those of fish PKZ than to the PKR kinase domains of other vertebrate species [30]. The similarity in structure inferred the analogy in functions.…”
Section: Discussionmentioning
confidence: 92%
“…The similarity in structure inferred the analogy in functions. Both PKZ and PKR are present in zebrafish, and both of them can phosphorylate eIF2a in yeast [30]. In other fishes, either PKZ or PKR is reported.…”
Section: Discussionmentioning
confidence: 99%